Effects of hydrogen on microstructure evolution and mechanical properties of TB8 titanium alloy - Yequan Chen; Shiying Wang; Jiaxing Meng; Naotoshi Mitsuzaki; Zhidong Chen (PLoS ONE, 2025)
The influence of varying hydrogen content on the microstructure, mechanical properties, and fracture behavior of the metastable β titanium alloy TB8 after hydrogen charging has been investigated in this study. Several characterization methods, including optical microscopy (OM), x-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM), were employed to comprehensively analyze the alloy. The results show that with the addition of hydrogen, hydrogen mainly accumulated at grain boundaries in the form of hydrides. The β phase diffraction peak shifted to a lower angle, which can be attribute to hydrogen-induced lattice distortion. As the hydrogen content increases, γ-TiH hydrides and ε-TiH2 hydrides were observed. Ultimate tensile strength of the alloy firstly increased from 982 MPa to 1636 MPa, and then decreased to 1432 MPa. Uniform elongation decreased from 33% to 19%. Fracture mode transitioned from ductile to brittle with increasing hydrogen. In summary, we hope the outcome of this work could provide important insights toward the hydrogen charging influences the microstructure, mechanical properties, and fracture behavior of the TB8 titanium alloy.